What matters for organisational change? Evidence from DEPZ, Bangladesh - Md. Zohurul Islam (SA Journal of Human Resource Management, 2013)
Orientation: The role of leadership and human resources (HRM) at the managerial level in the economic zones to implement organisational change have been well described in developing countries although they are often not well documented.